Digital Da'wah through YouTube Podcasts: Shaping Social Awareness among Adolescents in Deli Serdang, North Sumatera - Batoebara, Maria Ulfa; Lubis, Muya Syaroh Iwanda; Dimas Dwi Nugroho (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Podcasts have emerged as a flexible audio-visual medium that surpasses conventional radio through their play-on-demand feature, allowing audiences—particularly the Millennial and Gen Z cohorts—to consume content according to their own preferences and pace. Among adolescent communities such as those in Paya Geli Village, this flexibility is especially significant, as teenagers are known for their short attention spans and constant pursuit of novel forms of entertainment and information. Despite the proliferation of studies on social media's influence on adolescent behavior, limited scholarly attention has been paid to how personal narrative-based YouTube podcasts—such as the Gritte Agatha Podcast, which addresses themes of resilience, family relationships, and everyday social struggles—function as a medium for cultivating adolescent self-awareness. This gap is particularly notable given the podcast's popularity and its potential pedagogical value in shaping character and social consciousness among youth, an area that remains underexplored in Indonesian communication studies. This study addresses that gap by examining the role of the Gritte Agatha YouTube podcast in enhancing adolescent awareness in Paya Geli Village, investigating both the extent to which the podcast contributes to increasing adolescent awareness and the level of adolescent interest in and engagement with its content. Employing a qualitative descriptive method, this research aims to provide an in-depth account of these phenomena, identifying patterns and developments that allow for meaningful comparison and evaluation. The findings reveal that the Gritte Agatha podcast exerts a substantial influence on adolescent audiences, offering insights and vicarious experiences that viewers actively internalize and apply in their daily lives. These results underscore the novelty of positioning digital podcasting as an informal yet impactful medium of adolescent moral and social education—an area meriting further empirical attention in dakwah and communication research.